(untitled) (Fiep Bulletin - online, 2013)
The improvement of motor development is being treated as a new standard of health for the elderly, since factors such as disease, lack of autonomy, cultural factors, socioeconomic and lifestyle undertake the functional capacity of the individual for failing to preserve or to improve motor capacity, compromising thus the well-being and a healthy aging process. This research focused on evaluating and identifying whether or not the motor development was satisfactory according to the chronological age of the elderly women attending the University Center of UniEVANGÉLICA in Anapolis, Goias. The specific objectives were to evaluate fine motor skill, gross motor skill, balance, body schema, temporal organization and spatial organization in elderly between 60 and 75 years old. In order to obtain information, tests were used to assess the physical and motor conditions. The protocol used was the Motor Scale for the Elderly (EMTI) from Rosa Neto (2009). The results show that only the age was not statistically different, which is very important to emphasize the homogeneity of the group on this feature, since with advancing age there is a tendency to lose motor skills, as stated by NETTO (2007 ). In all other motor variables assessed, the elderly women achieved marks significantly lower than expected for their chronological range. It was concluded that all the elderly have their motor development much lower than expected for their chronological age, therefore it is unsatisfactory. Over the years there is a motor component’s regression in most elderly people, but this sample shows results much lower than the normal for this age group. The suggestion is to practice physical exercisse to provide fewer losses and reductions of motor components, enabling successful aging, allowing the development every day activities.